The wellbeing of nations : meaning, motive and measurement - Allin, Paul.; Hand, D. J. (David John) (Chichester, West Sussex, United Kingdom : Wiley, 2014)
'What is national wellbeing and what is progress? Why measure these definitions? Why are measures beyond economic performance needed and how will they be used? How do we measure national wellbeing & turn the definitions into observable quantities? Where are we now and where to next? These questions are asked and answered in this much needed, timely book. The Wellbeing of Nations provides an accessible and comprehensive overview of the measurement of national well-being, examining whether national wellbeing is more than the sum of the wellbeing of everyone in the country, and identifying and reviewing requirements for new measures. It begins with definitions, describes how to operationalize those definitions, and takes a critical look at the uses to which such measures are to be put. The authors examine initiatives from around the world, using the UK'measuring national wellbeing programme' as a case study throughout the book, along with case studies drawn from other countries, as well as discussion of the position in some countries not yet drawn into the national wellbeing scene'--
'Provides signposting to resources to be used in the development of sources, analyses and summary measures of national wellbeing and progress'--
Machine generated contents note: Chapter 1: What is national wellbeing and why measure it? 1.1 Motivation: Why measure wellbeing? 1.2 What is individual wellbeing? 1.3 Aspects of individual wellbeing 1.4 How to measure individual wellbeing 1.4.1 Basics of measurement 1.4.2 What is measured matters 1.5 Properties of measurements 1.5.1 Validity 1.5.2 Reliability 1.6 Objective or subjective? 1.7 Combining multiple aspects 1.8 What is national wellbeing? 1.9 And how to measure national wellbeing 1.10 Structure of the book References Chapter 2: A short history of national wellbeing and its measurement 2.1 The good society and philosophies of the role of government, from ancient times 2.2 Utilitarianism 2.3 The American constitution 2.4 Official statistics -- statistics about the state and about the state of society 2.5 National accounts and GDP 2.6 More to life than GDP 2.7 Social indicator movement and measuring quality of life 2.8 Health and wellbeing 2.9 Rise of measurement of psychological wellbeing (life satisfaction, happiness, worthwhile lives) 2.10 The Easterlin paradox 2.11 Taking note of the change in the quality of the goods and services we use 2.12 Capabilities approach to quality of life (Sen) and the Human Development Index 2.13 Social capital and public value 2.14 Limits to growth and sustainable development indicators 2.15 Commentary References Chapter 3: Recent developments: towards economic, social and environmental accounts 3.1 Mis-measuring our lives: the report by the Commission on the Measurement of Economic Performance and Social Progress 3.2 Replacing the Millennium Development Goals 3.3 A new global movement? 3.4 Commentary References Chapter 4: Measuring individual wellbeing 4.1 On quantification 4.2 Single measures of wellbeing 4.3 Combining aspects of wellbeing 4.3.1 Causes, effects, and correlates 4.3.2 Subjective components of wellbeing 4.3.3 Weighted sums 4.4 Components of individual wellbeing 4.5 The frailty of memory 4.6 The devil's in the details 4.7 Conclusion References Chapter 5: Preparing to measure national wellbeing 5.1 Towards a user requirement for measures of national wellbeing and progress 5.2 Towards a framework to measure the progress of societies 5.3 Constructing measures of progress and national wellbeing: identifying and meeting user requirements 5.4 Commentary References Chapter 6. How to measure national wellbeing 6.1 Drawing on the national economic accounts 6.2 Extending the national accounts 6.3 Indicator sets describing social and environmental conditions relating to wellbeing 6.4 Survey-based data on subjective wellbeing 6.5 Developments in measuring national wellbeing and progress around the world 6.6 Important issues in the measurement of national wellbeing References Chapter 7: Wellbeing policy and measurement in the UK Chapter 8: Conclusions 8.1 Progress? 8.2 Measuring wellbeing 8.3 New technologies, new data 8.4 Beyond the economy 8.5 The future References Annex: Sources of methods and measures of wellbeing and progress Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Happiness; Well-being.; Cost and standard of living; National income -- Accounting; BUSINESS & ECONOMICS -- Econometrics; Cost and standard of living; Happiness; National income -- Accounting; Well-being.; Electronic books